(untitled) (Albayan Scientific Journal, 2024)
This study was conducted on wild olives (Olea europaea L., var. sylvestris) with the aim of studying the morphological differences of wild types spread in the Jabal al-Akhdar region in northern Libya. The study area was divided into twelve regions separated by 10 km at different altitudes from sea level, and four trees were randomly selected from each region. The study’s results were subjected to variance and standard deviation analysis, which showed phenotypic variation between the types present in the study area at all the studied characteristics in terms of Fruit volume, Fruit weight, Fruit length, Fruit diameter, Fruit shape, flesh weight, flesh /fruit miss, Pit volume, Pit weight, Pit length, Pit diameter, Pit shapes index, and Flesh pit mass ratio that shows the presence of genetic diversity between the wild olive types spread in the study area. This allows these types to be used as a source of germplasm that is used to increase the desired characteristics such as fruit size, oil content, production, and resistance to environmental and biological conditions to improve and breed olives.